Kewenangan PTUN dalam Memeriksa Surat Presiden tentang RUU Cipta Kerja dan Implikasi Putusannya - Surya Mukti Pratama; Adrian E. Rompis; R. Adi Nurzaman (Fakultas Hukum Universitas Mulawarman, 2021)
For the first time, the President's Letter in the formation of law was sued by the Administrative Court. This study is intended to determine the authority of the Administrative Court in examining the President's Letter on the Job Creation Bill. The research method uses a normative juridical method using a law approach and a case approach. Based on the results of the research, it is known that the Administrative Court lacks absolute authority to investigate the Presidential Letter on the Job Creation Bill because the Presidential Letter does not meet the requirements specified in the law to qualify as the object of the TUN dispute, namely the state administrative decision (KTUN)/Beschikking. It can also be seen, that even if the decision of the Administrative Court or the court of appeal and cassation within the framework of Judicial Activism accepts and grants the lawsuit of the President's Letter regarding the Job Creation Bill, the decision cannot have direct implications for the invalidity of the validity/legitimacy of Law Number 11 of 2020 concerning Job Creation because the cancellation of the validity/legitimacy of a law is not under the authority of the Administrative Court, the PT-TUN includes the Supreme Court, but the authority of the Constitutional Court through material and formal examinations. The Job Creaton Act is still regarded as legal and binding if the Constitutional Court does not invalidate it. Keywords: Administratif Court; authority; examine; presidential letter.